2019
DOI: 10.1051/matecconf/201928004007
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Plastic Waste Polyethylene Terephthalate (Pet) as a Coarse Aggregate Alternative in Paving Block

Abstract: PET plastic waste is found everywhere in Banjarbaru City compared to other plastic wastes. It is an excellent prospect to reuse the PET plastic waste. The demand of mountain rock and stone from natural resources increases as happened in Aranio Sub District, Banjar Regency. This research is expected to find one way of suppressing the growth of the number of stone mines or natural stone. Based on SNI 03-0691-1996, the classification of the paving block differentiated according to its usage class, one of which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
(2 reference statements)
1
5
0
Order By: Relevance
“…At 28 days, compressive strength for concrete containing 5%, 10%, 15%, 25%, 50%, 75% and 100% was 44.14MPa, 30.22MPa, 15.37MPa, 39.98MPa and 28.19MPa respectively. A similar trend was observed by (4). However, at 5% replacement ratio, the paving blocks can be used in medium traffic areas since the compressive strength is above 40MsPa.…”
Section: Fig6: Compressive Strengthsupporting
confidence: 80%
See 1 more Smart Citation
“…At 28 days, compressive strength for concrete containing 5%, 10%, 15%, 25%, 50%, 75% and 100% was 44.14MPa, 30.22MPa, 15.37MPa, 39.98MPa and 28.19MPa respectively. A similar trend was observed by (4). However, at 5% replacement ratio, the paving blocks can be used in medium traffic areas since the compressive strength is above 40MsPa.…”
Section: Fig6: Compressive Strengthsupporting
confidence: 80%
“…Polyethylene Terephthalate (PET) is a plastic resin and the most common type of polyester. It is one of the common consumer plastic used and is widely employed as raw material products such as mineral water bottles, soft drink bottles, containers for packaging of food and other consumer goods(6)A study by (4) showed that, for a mix design of 1:4:6 (cement, fine aggregate, coarse aggregate), replacing coarse aggregates with PET at 25% produced concrete paving blocks with 15MPa compressive strength which was suitable for use in pedestrian areas.…”
Section: Iintroductionmentioning
confidence: 99%
“…The making of test specimens totals 15 pieces. The size of 20 × 10 × 8 cm with the ratio of cement material, fine aggregate, and coarse aggregates is 1:6:4 according to previous research by [12] which concludes that this is the right material comparison for coarse aggregate testing. The amount of PET as the independent variable is 0%, 25%, 50%, 75% and 100% against the coarse aggregate ratio used.…”
Section: Research Resultsmentioning
confidence: 57%
“…The manufacture of the specimens done in a private concrete plant. Total test specimens were 15 specimens, there were five different aggregate content of different plastic waste, with the correct composition based on [12] research on cement, fine aggregate and coarse aggregate, i.e., 1:6:4. The paving block manufacture using the compressive pressing machine.…”
Section: Manufacture Of Test Specimensmentioning
confidence: 99%
“…In Ecuador, there has been little research on the use of PET as an alternative material in construction. Nonetheless, a study has proposed an innovative and ecological technology in the elaboration of aggregate for cobblestones in the city of Quito due to a large number of PET plastic bottles [17], [18]. The construction of construction materials whose mixing composition contains recycled PET, saves costs and generates durability benefits compared to traditionally prepared materials [19]- [21].…”
Section: Introductionmentioning
confidence: 99%